An original experimental approach showing that most nonlinearities expressed by filled elastomers relate to microscopic friction and cavitation. Issue 9 (29th September 2020) - Picquart, Marion; Poirey, Gilles; Puel, Guillaume; Aubry, Denis
Abstract: Filled elastomers present a highly nonlinear behavior when submitted to cyclic mechanical loads. Origins of these nonlinearities are still uncertain, but many models rely on micromechanisms such as friction or cavitation at the filler/binder interface. To substantiate these hypotheses, an experimental approach is proposed to assess the real effects of friction and cavitation on the macroscopic response of filled elastomers. A linear, viscoelastic, transparent material is used to create macroscopic samples in which mechanisms are activated, separately or jointly. The response of these samples to cyclic mechanical loads shows that each mechanism generates some typical nonlinearities. A deeper analysis of the resulting curves allows a correlation between the nonlinearities characteristics (shapes and amplitudes) and the ones expressed by filled elastomers, providing clues for the development of future models. Abstract :